Single-laboratory validation of determination of acetaldehyde, ethyl acetate, methanol and fusel alcohols in wine spirits, brandies and grape marc spirits using GC-FID - Luís,Ana Catarina P. M. N. (2011)
This work presents the determination of principal volatile compounds (acetaldehyde, ethyl acetate, methanol, 2-butanol, 1-propanol, 2-methyl-1-propanol, 2-propen-1-ol, 1-butanol, 2-methyl-1-butanol and 3-methyl-1-butanol) in wine spirits and grape marc spirits by GC-FID. The method was evaluated in terms of suitability of chromatographic system, accuracy, precision, linearity and detection and quantification limits. The method showed good accuracy for the majority of the compounds and it presented linearity and precision for all compounds. Bases in these results the method seems suitable for quality control of marc spirits and wine spirits.